Determinan Manajemen Laba Perusahaan di Sektor Konsumsi - Muhammad Fajri (Ekonomis: Journal of Economics and Business, 2019)
The aim of this research is to provide empirical evidence on the impact of good corporate governance, free cash flow, and leverage ratio on earnings management. Good corporate governance is measured by audit committee’s size, the proportion of independent commissioners, institutional ownership, and managerial ownership. Discretionary accrual is the proxy of earning management. This research used 28 consumer goods companies listed in Indonesia Stock Exchange from 2016 to 2018. Data were analyzed using panel data with random effect model. Based on the result of analysis concluded that all components of good corporate governance (audit committee’s size, the proportion of independent commissioners, institutional ownership, and managerial ownership), have no significant effect on earnings management, on other hand leverage ratio has a negative effect and no significant on earning management, and free cash flow has a positve and no significant effect on earnings management